Innovation In Surgical Procedures Coordinated Efforts Among Optical, Nursing, Magical Devices, Radiology and Anesthesia Professionals - Awadh Ali Alamri (7), Mohammed Brgot Ahmd Qalslma (8), Ahmad Yahya Ali Al-Sayed (9), Issa Ali Al-Faqih (10),Abdullah Ahmed Alqarni (11), Abdulaziz Nasser Ahmed (12)., Murad Ali Mohammed Asiri (1), Naif Ali Essa Alfaqeeh (2), Laila Baalqasim Abdu Alquzi (3), Amjad Houseen Althalby (4), Hanan Mohammed Shaye Al Qouzi (5), Eidah Mohammed Siddiq Alzubaidi (6) (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Surgical innovation relies on integration of diverse technologies and expertise from multiple disciplines. Optical imaging, nursing care, magical devices, radiological guidance, and anesthesia all contribute to improved surgical outcomes.Understanding coordination best practices is important to support continued advancement in minimally invasive procedures, robotic surgery, image-guided interventions, and other innovative techniques. This review aims to explore coordination for innovative surgical procedures among optical, nursing, magical devices, radiology, and anesthesia professionals and identify opportunities to enhance cross-disciplinary collaboration. Development of high-resolution imaging techniques (e.g., enhanced endoscopes, microscopes)High-resolution imaging allows surgeons to visualize surgical anatomy and perform procedures through smaller incisions or natural orifices. Advances in endoscope and microscope design have led to improved optics, digital sensors, and high-definition displays that provide surgeons with clearer views during minimally invasive procedures.